Re-imagining the nation - Mngomezulu, Nosipho Sthabiso Thandiwe (Rhodes University, Faculty of Humanities, Department of Anthropology, 2015)
This thesis examines young people's constructions of nationhood in Mauritius. In 2008, the Mauritian government instituted a Truth and Justice Commission (TJC), set up to investigate the consequences of slavery and indentured labour. Through the Truth and Justice Commission, the Mauritian government indicated its desire to achieve social justice and national unity. Drawing on developments in studies of national identification practices in the 21st Century, this thesis addresses the question of young Mauritian's locally and globally informed identification practices and asks how their unofficial narratives of nationhood challenge, or divert, or relate to official state narratives of nationhood. The basis of the study emerges from data collected from 132 participants during fieldwork in multiple fieldsites from May to September 2010 as well as research on Mauritian youth on-line from 2011-2014. The advent of the TJC offers an ideal moment to evaluate the dynamics of post-colonial nation-building and nationhood in a selfstyled multi-cultural state. Nationhood, does not exist apriori to the constructions of narratives of the nation, thus the stories told about the nation, imagine the nation into being. By situating the Truth and Justice Commission and other official state narratives alongside young people's narratives, I argue that contemporary narratives of nationhood in Mauritius represent an intergenerational struggle to define the meaning of the past in the present and consequently outline the future. Reflecting on the ideas and socio-economic and political processes that induce national consciousness, I argue that young people's narratives of everyday lived experiences are vital for an interpretation of how nationhood is produced in everyday life. The cultural projects of young people "“ often rendered as liminal or marginal "“ offer a critical vantage point from where to read constructions of nationhood. Far from being growing pains or childish games, young people's identity making practices are what Sherry B. Ortner has called "serious games." This research suggests that official state government narratives of multicultural nationhood in Mauritius narrowly define national identification along communal loyalties, overlooking the dynamism of interculturality and transnationalism in daily practice on the island. Although communalism and rigid colonial interpretations of ethnicity attempt to police and limit the possibilities of alternative modes of being in Mauritius, young people's identification practices question, challenge, and threaten to disrupt official discourses of ethnic identification in Mauritius Scholarly investigations of young peoples' lived experiences of nationhood extend theoretical and methodological frames for the study of nationalized subjects and deepen the understanding of the construction of national consciousness. The construction of nationhood always involves narratives of some sort "“ scholarship on this area has usually focused on official state narratives from social theorists, state governments, and state elites. I argue for the importance of considering subjectivity and lived experience in conceptions of nationhood. In contemporary post-colonial societies, young people are the numerical majority, however, their voices are seldom represented in theories and narratives of nationhood. Whilst young people may appear in state policies (especially education) and official narratives about the future of the nation, their creative imagining and reimagining of narratives of selfhood is often ignored. I examine how young people increasingly are aware of their transnational connections, through participation in transnational youth cultures, and they are consequently increasingly multi-lingual and multicultural. Fixed notions of ethnic identification and discourses of trauma are not at the forefront of young people's identification of selfhood, rather their ability to take advantage of their multiply situated identification processes allows them new means to evade and transform these narratives. Their identification of selfhood is characterised by a greater degree of dynamism than previous generations had access to, and thus they do not only identify themselves through officially sanctioned national forms of identification. Loyalty to nationhood is thus less predictable, and young people represent a potential threat to the continuation of older forms of nationhood. While official narratives of nationhood may manipulate ethnic and racial cleavages to secure old loyalties, not all young people are persuaded by these notions
Keywords: Mauritius -- Truth and Justice Commission; Nationalism -- Mauritius; National characteristics, Mauritian; Social justice -- Mauritius; Youth -- Mauritius -- Social conditions; Youth -- Mauritius -- Attitudes; Mauritius -- Politics and government -- 1992-; Ethnicity -- Mauritius